A Chinese Perspective on Economic Development: The Views of Justin Yifu Lin. (1st September 2013) - Garnaut, Ross
Abstract: An intellectually vigorous modern economics profession has emerged in China over the past three decades of market‐oriented reform and opening to the international economy. Understanding the Chinese economy is essential to understanding economics as China approaches being the world's largest economy. This review article discusses the modern economics profession in China and the contributions of Professor Justin Yifu Lin, a pioneer of modern economics in China and a major contributor from the beginning until now. It introduces and describes the distinctive ideas in his four recent books in English, which make his ideas and work accessible to economists outside China .